Agricultural dust explosions in 2004 - Schoeff, Robert W. (Kansas State University. Dept. of Grain Science and Industry, 2010)
There were six dust explosions reported in the U.S. in 2004 according to Robert W. Schoeff, Professor Emeritus, Kansas State University, and Mavis Rogers, FGIS-USDA. This compares to 7 in 2003 and a tenyear average of 10.1 explosions.
Keywords: Grain dust; Dust explosions